Quality Analysis of Pre-Release Rice Cultivars - Sheena Kandathil M (Department of Home Science, College of Agriculture, 1997)
The ‘Quality analysis of pre – release rice cultivars’ were determined by assessing their physical characteristics, cooking characteristics, nutritional composition and organoleptic qualities. The effect of parboiling on the above quality aspects were also studied. Among the physical characteristics, thousand grain weight was found to be higher for the variety M – 45 – 20 -1. Lower moisture content was observed in variety M-38-4-2. Higher percentage of head rice yield was observed in the variety M-57-18-1-1. Parboiling significantly increased the thousand grain weight and head rice yield of rice varieties, while moisture content and L/B ratio was found to be decreased after parboiling. The cooking characteristics of rice varieties with reference to optimum cooking time and gruel loss was higher in M-38-4-1 and M-57-18-1-1 respectively. The variety M-38-4-1 had a significantly higher volume expansion ratio, when compared to the other varieties. Varieties Cul -87117, M - 45 – 20- 1 and M - 42 -6 - 3 have intermediate amylose content. Parboiling had a positive influence on the cooking characteristics of rice varieties. Compared to other varieties, M – 38 – 4 - 2 had obtained higher values for nutritional characteristics such as protein, phosphorus, calcium and iron content. Variety M - 38 - 4 - 1 had the highest calorific value. Parboiling significantly increased the cooking characteristics except protein and starch content. From the organoleptic evaluation of cooked rice, it was found that M - 38 - 4 - 2 was more acceptable with respect to five quality attributes such as colour, appearance, flavour, texture and taste. Based on physical, cooking, nutritional and organoleptic qualities, discriminant function analysis was carried out and it was found that variety MO - 1 - 20 – 19 – 4 was the superior variety in both raw and parboiled forms.